LITERASI FISIK DAN SPORTSMANSHIP GURU PJOK DI PASURUAN - Nova Maqamah; Nurcholis Sunuyeko; Agung Yuda Aswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical inactivity remains a global health issue that highlights the strategic role of Physical Education, Sport, and Health (PJOK) teachers in promoting an active, healthy, and sportsmanlike lifestyle. PJOK teachers are required not only to possess technical skills in sports but also to demonstrate physical literacy and Sportsmanship  attitudes that support the development of positive values in physical education learning. This study aimed to examine the physical literacy and Sportsmanship  attitudes of PJOK teachers in Pasuruan based on good-category criteria and to analyze the relationship between physical literacy and Sportsmanship  attitudes. This research employed a quantitative approach with a descriptive-comparative and correlational design. Primary data were collected using a closed-ended questionnaire based on a five-point Likert scale from 152 PJOK teachers selected through snowball sampling. Physical literacy was measured using the Perceived Physical Literacy Instrument (PPLI) developed by Sum et al. (2016), while Sportsmanship  attitudes were measured using an instrument adapted from the Multidimensional Sportspersonship Orientations Scale (MSOS) developed by Vallerand et al. (1997). Data were analyzed using the One-sample t-test and Pearson correlation. The results showed that the mean score of teachers’ physical literacy was 79.19, which was significantly higher than the reference value of 61.2, with a mean difference of 17.991 and p < 0.001. The mean score of Sportsmanship  attitudes was 112.37, which was also significantly higher than the reference value of 85, with a mean difference of 27.368 and p < 0.001. Pearson correlation analysis indicated a strong, positive, and significant relationship between physical literacy and Sportsmanship  attitudes, with r = 0.749 and p < 0.001. These findings indicate that the physical literacy and Sportsmanship  attitudes of PJOK teachers in Pasuruan have met the good-category criteria. Furthermore, higher physical literacy tends to be associated with better Sportsmanship  attitudes. This study emphasizes the importance of strengthening teachers’ physical literacy as a foundation for developing Sportsmanship  values in physical education learning.